Resistance exercise as a treatment for sarcopenia: prescription and delivery. (12th February 2022) - Hurst, Christopher; Robinson, Sian M; Witham, Miles D; Dodds, Richard M; Granic, Antoneta; Buckland, Charlotte; De Biase, Sarah; Finnegan, Susanne; Rochester, Lynn; Skelton, Dawn A; Sayer, Avan A
Abstract: Sarcopenia is a generalised skeletal muscle disorder characterised by reduced muscle strength and mass and associated with a range of negative health outcomes. Currently, resistance exercise (RE) is recommended as the first-line treatment for counteracting the deleterious consequences of sarcopenia in older adults. However, whilst there is considerable evidence demonstrating that RE is an effective intervention for improving muscle strength and function in healthy older adults, much less is known about its benefits in older people living with sarcopenia. Furthermore, evidence for its optimal prescription and delivery is very limited and any potential benefits of RE are unlikely to be realised in the absence of an appropriate exercise dose. We provide a summary of the underlying principles of effective RE prescription (specificity, overload and progression) and discuss the main variables (training frequency, exercise selection, exercise intensity, exercise volume and rest periods) that can be manipulated when designing RE programmes. Following this, we propose that an RE programme that consists of two exercise sessions per week and involves a combination of upper- and lower-body exercises performed with a relatively high degree of effort for 1–3 sets of 6–12 repetitions is appropriate as a treatment for sarcopenia. The principles of RE prescription outlined here and the proposed RE programme presented in this paper provide a useful resource for clinicians and exercise practitioners treating older adults with sarcopenia and will also be of value to researchers for standardising approaches to RE interventions in future sarcopenia studies.